Examining the Impact of Bank Health on Profit Growth among Infobank15-Listed Banks - Kusumawardani, Ida Ayu Jayanti; Hasibuan, Henny Triyana (E-Jurnal Akuntansi; Vol 34 No 7 (2024), 2024)
Banking institutions make a critical contribution to the economy by aiming to maximize profits for efficient operations. This study evaluates the impact of several key financial ratios—Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Good Corporate Governance (GCG), Return on Assets (ROA), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR)—on the profit growth of banks listed in Infobank15 from 2019 to 2022. Using a saturated sampling technique, data from 26 companies, resulting in 104 observations, were analyzed through multiple linear regression. The results indicate that LDR, GCG, ROA, NIM, and CAR have a positive and significant impact on profit growth, while NPL negatively and significantly affects it. These findings underscore the importance of regular financial ratio reviews to manage bank health and enhance performance. Data were sourced from annual reports and analyzed using the Risk-Based Bank Rating (RGEC) approach mandated by Bank Indonesia Regulation No. 13/1/PBI/2011. Keywords: Risk profile; Good Corporate Governance; Earnings; Capital; Profit Growth